Penerapan PSAK No. 45 Pada Laporan Keuangan Nirlaba di Yayasan Pendidikan Diniyyah Putri Lampung - Pandhu I Sukmantoro; Evi Ekawati (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2021)
Purpose: This study aimed to ascertain how the Diniyyah Putri Education Foundation prepares its financial statements and conducts a review of the preparation results. Research Methodology: The qualitative method was used in this study, with a case study approach. Results: Diniyyah Putri Education Foundation did not follow PSAK 45 in its financial reporting in this study. Contribution: This research contributes to non-profit organizations in Indonesia by instructing them how to prepare financial statements according to Indonesian law, specifically PSAK No. 45.